Finnish agri-food sector outlook 2021 - (:unkn) unknown (Natural Resources Institute Finland (Luke), 2021)
Finland’s economic decline gentler than expected Finland’s economy survived the first year of the coronavirus fairly well compared with many other countries. In 2020, the economy decreased by less than 3%, which was significantly less than was estimated in the spring of 2020. Keeping the epidemic well under control in Finland had the highest impact on the positive performance. Economic recovery, both in Finland and globally, ultimately depends on the rapid progress of vaccinations and the successful suppression of the coronavirus pandemic. National recovery measures and the upcoming EU recovery package support economic growth. Recovery is especially expected to come from growing demand for services, as households’ pent-up desire to consume starts to unwind after the epidemic. This would also help the foodservice industry, restaurants and the out-of-home sector, which were struck hardest by the coronavirus epidemic, to get back on their feet. The coronavirus year affected food purchasing and consumption behaviour The coronavirus year increased cooking and baking at home. Households purchased more food from grocery stores. Sales of food and non-alcoholic beverages increased by 7%, while sales of certain food products grew by more than 15%. The increase in sales in euros can mainly be explained by the increase in volumes, as the increase in food prices was only 1.7%. Based on the preliminary data of the Balance Sheet for Food Commodi¬ties published by the Natural Resources Institute Finland (Luke), changes in the total consumption of food were moderate in 2020, as in previous years. Consumption is expected to become polarised, because demand is high for both basic low-cost foodstuffs and value-added products. More cooking experiences are sought especially from spicy food. Last year, sales of organic products increased by nearly 10%, but they still only account for 3% of total sales. Trade deficit decreased The value of Finland’s food exports increased slightly in 2020. The value of food exports from Finland totalled EUR 1,739 million, up by 1.3% from the previous year. Correspondingly, the value of food imports to Finland was EUR 5,295 million, practically the 2019 level, with growth only less than 0.1%. Following the years of high growth at the beginning of the millennium, growth in imports started to slow in 2013 and has nearly halted after 2017. Common Agricultural Policy to be reformed The European Council’s agreement on the EU’s multiannual financial framework (MFF) in July 2020 propelled negotiations on the reform of the Common Agricultural Policy (CAP) a crucial step forward. However, the new policy will not be implemented in the EU states until 2023. In 2021-2022, the agricultural policy for the previous 2014-2020 period will be followed, while funding will be drawn from the CAP’s budget allocation for 2021-2027. Funding provided for agriculture in Finland will increase during the new funding period as a result of the July 2020 budget agreement. The national strategy plan for the agricultural policy is prepared during 2021. The Euro¬pean Commission is expected to handle and confirm the plan in 2022. Winter wheat accounting for a growing part of the cultivation area Cereal production is stable in Finland, exceeding domestic needs. Barley and oats continue to be clearly the largest crops measured by production volume. Their cultivation areas are not expected to change significantly during the upcoming harvest season. The proportion of winter wheat from the total wheat area is increasing. Rye is increasingly being produced on the basis of production agreements. Imports of oats are growing steeply, both in the form of grains and milled industry products. Self-sufficiency in proteins to be increased In recent years, the cultivation of peas has especially increased. Instead, the general interest in the cultivation of turnip rape and rapeseed, as well as broad beans, has decreased due to increased uncertainties concerning cultivation and lower yields. Although the total self-sufficiency rate in plant protein is high in Finland, the self-sufficiency rate in the complemen¬tary proteins required for livestock was lower than ever before in 2020. Improving self-sufficiency is a common goal in the crop and livestock sectors. Oil and protein crops also provide farmers with significant benefits through crop rotation and profitability. Poultry and pork production increasing In Finland, meat production is increasing, driven especially by the growing production of poultry meat and pork. Poultry production is sped up by domestic markets, and pork production by Chinese export markets. The significant positive increase in the pork trade balance is one of the most notable phenomena. The meat self-sufficiency rate increased significantly in 2020 as a result of growing production, and it is also expected to increase slightly this year, approaching 100%. However, the self-sufficiency rate shows considerable differences by type of meat. Total meat consumption per capita has evened out in recent years to 79-80 kilograms. Milk exports increased; imports decreased Demand for domestic dairy products was high in 2020. Supermarket sales of dairy products increased during every quarter, driven by the coronavirus restrictions, compared with corresponding periods in the previous year. However, demand for dairy products consumed in food services decreased due to the coronavirus restrictions. The milk trade balance increased as a result of increased exports and decreased imports. The average producer price increased slightly from the previous year, at a little more than 39 cents per litre. Total milk production increased by 1.4% to 2,293 million litres. The structural change continued to be rapid, with 7% of farms discontinuing their production operations during the year. At the end of the year, milk was produced on 5,566 farms, 139 of which were organic. Valio Group’s transi¬tion to contractual milk production at the beginning of 2021 will hold back the total volume of milk production. During the first quarter of 2021, the total production volume was 3% lower than in the previous year. According to the Finnish Food Authority, this was already reflected in the investment subsidy applications of dairy farms at the end of 2020, after which applica¬tions have mainly concerned renovations, with larger projects awaiting the granting of agreements in the future. Proportion of free-range and organic eggs increasing In 2020, the consumption of eggs reached a new record during the 2000s, at 12.5 kilograms per consumer. This increase can be explained by consumers spending more time and cooking more at home. Currently, the consumption and production of eggs are well balanced, as a result of which producer prices of eggs have been fairly stable. Producer prices of eggs produced in enriched battery cages and barn henhouses increased by a few per cent, while those of free-range and organic eggs decreased slightly. The number of farms and production in enriched battery cages continue to decrease, while the average farm size is increasing. The horticultural sector overcame disruptions caused by the availability of workforce From the horticultural sector’s perspective, the 2020 season and the coro¬navirus epidemic revealed how much Finland’s horticultural production depended on foreign seasonal workers. Market chains for horticultural products also had to make rapid changes, as they needed to find new market channels for production intended for restaurants and workplace cafeterias. Yet households purchased more vegetables at retail shops, preferring Finnish production. On the basis of horticultural statistics, there was no slump in total production volumes and areas, even though some farms experienced problems and crops remained unharvested. Farms specialising, the number of farms decreasing, production remaining unchanged In 2020, there were approximately 45,400 agricultural and horticultural enterprises in Finland, which was 1,400 fewer than in the previous year. However, the decrease in the number of farms had no significant impact on production volumes. The agricultural land of discontinued farms transferred to new farms that continued previous operations. In addition, unit sizes increased on livestock farms. Farms have also become special¬ised and increased their production. For example, meat production has increased during the 2000s, although the number of livestock farms has decreased. Similarly, milk production has only decreased by a few per cent, even though the number of dairy farms has nearly halved from the situa¬tion ten years ago, and the number of dairy cows has decreased by more than a quarter during the 2000s. The proportion of combination farms has decreased in all livestock production lines. Increases in costs reduces the profitability of agriculture Luke’s profitability study indicates that enterprises do not, on average, produce added value for the capital invested in them. The total return on investment has been lower than interest on long-term state loans throughout the 2000s. In recent years, agricultural entrepreneurs have received a salary of EUR 7 per working hour, with net interest income from equity having been 1.6%. The decreased profitability also affects the loan servicing ability. During the 2000s, the relative indebtedness of farms has increased to nearly 90%. This is an alarming trend, as growing unit sizes take up more and more loan capital. At the same time, producer prices are only increasing slowly, while increased costs reduce profits and precon¬ditions for profitability. Farm expenses are fairly high relative to income. Entrepreneurial income reacts strongly to changes in costs. If all costs increase by 1%, the average entrepreneurial income of farms will decrease by nearly 9%. Cereal and beef farms are the most sensitive primary produc¬tion lines to changes in costs. Intensively searching for replacements for peat As the use of peat as energy is decreasing, there will be changes in the energy and bedding material use on farms and the impacts are reflected not only in agriculture but also in horticulture and particularly in green¬house cultivation. However, a strong decrease in the share of peat in energy consumption will not probably weaken the operating conditions of agriculture and horticulture in Finland. The price of peat used as a growing medium in horticulture will increase similarly to the pressure to find replacement solutions for peat as a growing medium. Peat also has several good qualities as bedding and enrichment material for animals which are difficult to replace by other alternatives. Animal rearing is searching for possible replacements for peat particularly from the side streams of agri¬culture and forestry. Significance of animal welfare increasing Farm animal welfare is an important part of the sustainability of animal production alongside economic and environmental sustainability. Packing labels can effectively inform consumers about food quality and sustaina¬bility. Animal welfare has become more important in food marketing and it is an issue that interests both consumers and companies. Even though welfare is increasingly emphasised in the marketing of food of animal origin, there is no comprehensive farm animal welfare label in the Finnish market. It is important for the success of an animal welfare label that consumers are interested in and aware of the welfare label, actors along the value chain are engaged in quality work extensively enough and the industry is willing to be transparent.
Keywords: agriculture and food markets; agricultural policy; production; consumption; profitability